A new control structure to reduce time delay of tracking sensors by applying an angular position sensor. (July 2016) - Yadegar, Meysam; Karami, Farzaneh; Nobari, Jafar H.
Abstract: In this paper, a new tracking control structure is proposed to decrease the time-delay effect of tracking sensor. To achieve this purpose, an angular position sensor, which generally exists in tracking systems, is used together with the tracking sensor. Also, a compensator is designed and applied to a system with time-delay in order to obtain a behavior same as a system without time-delay. Relying only on tracking sensor may lead to reduce the tracking speed and to increase tracking error. However, it is shown that by using the proposed reformative structure, the speed of tracking and the tracking error can be compensated significantly. In the next step, the performance of the new structure in two cases of constant time-delay and variable time-delay are evaluated and their stability conditions are analyzed. Finally, robustness of the proposed structure is analyzed. Highlights: A new tracking control structure to decrease the time-delay Inherent characteristic of tracking sensor is proposed. For a system with delay, a compensator is designed and applied to achieve behavior same as a free time-delay system. . The performance of new structure in two cases of delay is evaluated and their stability conditions are analyzed.